Premiumization as a Profit Growth Strategy - A Framework of Strategic Options - Anna-Karina Schmitz; Martin Faßnacht (Marketing Review St.Gallen, 2020)
Premiumization is an attractive growth strategy in competitive markets as it allows firms to achieve higher price levels by adding value to a brand or a brand portfolio. This article provides a conceptual framework of strategic options for premiumization and derives managerial guidelines on how to choose and successfully implement the right option.
Keywords: 650